2009
DOI: 10.2486/indhealth.47.569
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Respirators Usage for Airborne Chemicals in Korea

Abstract: A questionnaire survey was undertaken to identify the current status of respirator usage in manufacturing work environments subject to gas/vapor chemicals exposure in Korea and to suggest improvements to enhance the effectiveness of respirator usage. The number of target companies included 17 big companies, 110 small & mid-size companies, and 5 foreign companies, and the number of respondents included 601 workers and 69 persons in charge of respirators (PCR). The results explained clearly that respirator progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Furthermore, a study of Norwegian silicon carbide workers reported that only 74% used respirators some- or all of the time when in exposed areas (Føreland et al, 2008 ). Studies from other industrial settings also show that the use of respiratory protective equipment (RPE) is not always in accordance with regulations or necessity (Salazar et al, 2001 ; Carpenter et al, 2002 ; Bryce et al, 2008 ; MacFarlane et al, 2008 ; Mitchell and Schenker, 2008 ; Tam and Fung, 2008 ; Han and Kang, 2009 ; Guseva Canu et al, 2013 ). Thus, inadequate use of respirators does not appear to be exclusive to the Norwegian smelter industry.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study of Norwegian silicon carbide workers reported that only 74% used respirators some- or all of the time when in exposed areas (Føreland et al, 2008 ). Studies from other industrial settings also show that the use of respiratory protective equipment (RPE) is not always in accordance with regulations or necessity (Salazar et al, 2001 ; Carpenter et al, 2002 ; Bryce et al, 2008 ; MacFarlane et al, 2008 ; Mitchell and Schenker, 2008 ; Tam and Fung, 2008 ; Han and Kang, 2009 ; Guseva Canu et al, 2013 ). Thus, inadequate use of respirators does not appear to be exclusive to the Norwegian smelter industry.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the two most important outcome measures were participants' intention to use RPE and rate of respirator use. Several studies have concluded that the use of respiratory protective equipment is not optimal in construction, manufacturing, health care, nuclear industry, farming and hazardous waste management (Salazar et al, 2001;Carpenter et al, 2002;Bryce et al, 2008;MacFarlane et al, 2008;Mitchell and Schenker, 2008;Tam and Fung, 2008;Han and Kang, 2009;Guseva Canu et al, 2013). Our own results indicated that most respondents in the current study had a high level of intent to use respirators at baseline and that they used respirators most of the time spent in exposed areas.…”
Section: Discussionmentioning
confidence: 54%
“…Seventyeight percent of the workers report that they do not always use RPE in exposed situations . Sub-optimal RPE use has been reported in other professions such as nursing, farming, mining, construction and nuclear energy (Salazar et al, 2001;Carpenter et al, 2002;Bryce et al, 2008;MacFarlane et al, 2008;Mitchell and Schenker, 2008;Tam and Fung, 2008;Han and Kang, 2009;Guseva Canu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…RPP has been evaluated in other workplaces in previous studies. For example, a study in Korea showed that the status of respiratory protection in small and medium industries was poor [19] . In addition, the study by Honarbakhsh et al.…”
Section: Discussionmentioning
confidence: 99%